Investigation of the mechanism of the anti-cancer effects of Astragalus propinquus Schischkin and Pinellia pedatisecta Schott (A&P) on melanoma via network pharmacology and experimental verification - Fang Wang; Juan Bai; Feng Li; Jing Liu; Yanli Wang; Ning Li; Yaqi Wang; Jin Xu; Wanbao Liu; Liting Xu; Lin Chen (Frontiers Media S.A., 2022)
Melanoma is a commonly malignant cutaneous tumor in China. Astragalus propinquus Schischkin and Pinellia pedatisecta Schott (A&P) have been clinically used as adjunctive drugs in the treatment of malignant melanoma. However, the effect and mechanism of A&P on melanoma have yet to be explored. The current investigation seeks to characterize the active components of A&P and their potential roles in treating malignant melanoma using network pharmacology and in vitro and in vivo experiments. We first used the traditional Chinese medicine systems pharmacology (TCMSP) database and high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS) to identify a total of 13 effective compounds within A&P. 70 common genes were obtained by matching 487 potential genes of A&P with 464 melanoma-related genes, and then we built up protein-protein interaction (PPI) network of these 70 genes, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. The results revealed that A&P might influence the pathobiology of melanoma through the PI3K/Akt pathway. Molecular docking also confirmed that higher content of ingredients in A&P, including hederagenin, quercetin, beta-sitosterol and stigmasterol, had a strong binding activity (affinity < −5 kcal/mol) with the core targets AKT1, MAPK3 and ESR1. Furthermore, we confirmed A&P could inhibit melanoma cells proliferation and induce cells apoptosis through suppressing the PI3K/Akt signaling pathway by in vitro and in vivo xenograft model experiments. These findings indicate that A&P may function as a useful therapy for melanoma through the PI3K/Akt pathway.